Sistem Kendali Suhu dan Kelembaban Dengan Long Range Pada Kumbung Jamur Menggunakan Logika Fuzzy - Pratama, Indah Sari Putri; Suroso, Suroso; Agung, M. Zakuan (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Room temperature and humidity are parameters required for quality mushroom growth. To get the appropriate and stable temperature and humidity values, a control system is needed. This test aims to create a temperature and humidity control system using IoT-based fuzzy logic implementation. This temperature and humidity control system, uses the main components of DHT22 sensors, NodeMCU ESP32, Arduino nano and Lora. The transmitter is placed in the mushroom barn. The transmitter control system stabilizes the temperature and humidity in the barn using a predetermined fuzzy method. After that, the data processed at the transmitter will be sent to the receiver via Lora communication. At the receiver, the device is placed in the mushroom farmer's house, which will capture the data sent by the transmitter. This recognition system has a good level of accuracy against the DHT22 sensor and Hygrometer, which has a difference of 1℃ or a difference of 2.08%. In contrast, for humidity, it has a total difference of 16% or 97.61%. When testing using fuzzy logic, the resulting temperature and humidity are stable, and the predetermined fuzzy logic carries out watering.